Emissions of BTEXs, NMHC, PAHs, and PCDD/Fs from Co-processing of Oil-based Drilling Cuttings in Brick Kilns. (15th February 2022) - Liu, Tingting; Tian, Lifeng; Yang, Liuyang; Yan, Dahai; Huang, Qifei; Lu, Guilan; Liu, Zewei; Huang, Zechun
Abstract: Oil-based drilling cuttings (OBDC) produced from shale gas development is a hazardous waste that have high calorific values and should be disposed of properly. Burning bricks with OBDC is a promising co-disposal method; however, organic pollutants emitted during this process have not received sufficient attention. In this study, the composition and combustion characteristics of OBDC were determined, and the emissions of typical organic pollutants when burning bricks with the addition of OBDC were investigated; these included benzene series compounds (BTEXs), non-methane total hydrocarbons (NMHC), polycyclic aromatic hydrocarbons (PAHs), and polychlorinated dibenzo- p -dioxins and polychlorinated dibenzofurans (PCDD/Fs). The results showed that OBDC comprised large amounts of alkanes and aromatic hydrocarbons, and combusted mainly in the temperature range of 145–450 °C with an ignition temperature of 145 °C. The co-processing 10% OBDC increased the concentrations of toluene, NMHC, and PAHs in the flue gases by ∼1000%, ∼500%, and 200%, respectively, compared to the control experiment; however, their emission concentrations were within the limits set by the Integrated emission standards of air pollutants of Chongqing. It is worth noting that 26.443 ng/Nm 3 PCDD/Fs with a total toxicity of 0.709 ng I-TEQ/Nm 3 was generated from the co-processing 10% OBDC, which was ascribed to the high content of chlorine and aromatic hydrocarbons in the OBDC-promoted PCDD/Fs formed during the burning and cooling processes. Though PCDD/Fs in flue gas exceeded the 0.5 ng I-TEQ/Nm 3 limit prescribed in the Pollution control standard for hazardous wastes incineration of China, the realistic emission of PCDD/Fs is expected to meet with this emission limit after desulfurization treatment as PCDD/Fs can be absorbed by gypsum. It is recommended that a lower amount of OBDC is added to reduce PCDD/F formation at the source and to take more efficient air pollution control system in order to reach a stricter emission limit of 0.1 ng I-TEQ/Nm 3 in EU and USA. Cycling flue gas may also be an effective method to reduce other organic pollutants. Under these conditions, co-processing OBDC in brick kilns can be achieved without serious environmental pollution, making it a potential method for disposal and utilization. Graphical abstract: Image 1 Highlights: Higher/lower heating values of OBDC were 5.40/4.04 MJ/kg, ∼3 times of coal gangue. Organic matter in OBDC mainly comprised of alkanes and aromatic hydrocarbons. Co-processing OBDC in a brick kiln increased organic pollutant emissions. The BTEXs, NMHC, and PAHs in flue gas for OBDC group were below emission standard. PCDD/Fs in flue gas can be within limit of emission standard after desulfurization.